Morfoanatomia, tricomas glandulares e análise fitoquímica de Trichogonia eupatorioides (Gardner) R. M. King & H. Rob (ASTERACEAE-EUPATORIEAE) ocorrente em área de cerrado rupestre - Fernandes, Yanne Sousa (2014)
Cerrado rupestre is a subtype of arboreal-shrub vegetation that occurs in rupestrian and rocky habitats. Trichogonia eupatorioides (Gardner) R. M. King & H. Rob belongs to the tribe Eupatorieae of the family Asteraceae, and it is endemic to Brazil. Given the scant knowledge of the botanical traits of this species, the present study aimed to describe the morpho-anatomy of leaves and stems, characterize and identify developmental stages of glandular trichomes, detect the presence of metabolites by phytochemical screening, and determine the composition of the essential oil from aerial vegetative and reproductive parts of T. eupatorioides from a cerrado rupestre area. Samples of T. eupatorioides were collected from the Biological Reserve “Prof. José Ângelo Rizzo” of Universidade Federal de Goiás (UFG). Fully expanded leaves, stems, stem apices, flowers and involucral bracts were used for the morpho-anatomical study and to describe glandular trichomes. Aerial vegetative and reproductive organs were used for the phytochemical study. T. eupatorioides shares anatomical traits with other species described in the literature, such as amphistomatic leaves, anomocytic and anisocytic stomata, epidermal cells with sinuous anticlinal walls and thick external periclinal walls, glandular and non-glandular trichomes, endodermis with starch and Casparian strips, fibers associated to the vascular bundle, and secretory ducts. The glandular trichomes secrete essential oils and phenolic compounds and may be uniseriate or biseriate. The differentiation of the glandular trichomes begins with the expansion of a protodermal cell. The first division is anticlinal for biseriate trichomes, and periclinal for uniseriate ones. The phytochemical screening identified flavonoid and cardiac glycosides and coumarins. Twenty components of the essential oil were identified; of these, 95% were sesquiterpenes. The major components were the sesquiterpenes 3,5-muuroladiene (39.56%), butylated hydroxytoluene (13.07%), and (E)-caryophyllene (5.63%).